2001
DOI: 10.1046/j.0953-816x.2001.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP stimulation of P2X7 receptors activates three different ionic conductances on cultured mouse Schwann cells

Abstract: Extracellular ATP, by acting on P2 purinergic receptors, is a potent mediator of cell-to-cell communication both within and between the nervous and the immune systems. We show here by patch-clamp recording, fluorescent dye uptake and immunocytochemistry that, in cultured mouse Schwann cells, ATP activates a P2X(7) receptor associated with three different ionic conductances. In control conditions, ATP activated an inward current (I(ATP)) with a low potency (EC(50), 7.2 mM). Replacing ATP either by the ATP analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 36 publications
(34 reference statements)
4
42
0
Order By: Relevance
“…Previous studies have presented evidence that P2X7R are expressed in the paranodal membrane of rat Schwann cells in vivo [15], in cultured mouse Schwann cells [8,21,24], in longitudinal sciatic nerve sections of rat and mouse [20] and in cross and longitudinal sciatic nerve sections of mouse [12]. In this study, we clearly demonstrate localization of P2X7R ir in two types of Schwann cells in longitudinal sciatic nerve sections.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies have presented evidence that P2X7R are expressed in the paranodal membrane of rat Schwann cells in vivo [15], in cultured mouse Schwann cells [8,21,24], in longitudinal sciatic nerve sections of rat and mouse [20] and in cross and longitudinal sciatic nerve sections of mouse [12]. In this study, we clearly demonstrate localization of P2X7R ir in two types of Schwann cells in longitudinal sciatic nerve sections.…”
Section: Discussionsupporting
confidence: 53%
“…Early electrophysiological and pharmacological data showed that P2X7R are functionally expressed in myelinating Schwann cells of peripheral nerves [15]. With methods of patch-clamp recording, fluorescent dye uptake and immunocytochemistry, P2X7R were detected in cultured mouse Schwann cells [8]. Recent data has shown that P2X7R control myelination in sciatic nerves and contribute to the death of Schwann cells transplanted into the spinal cord [12,20].…”
Section: Introductionmentioning
confidence: 99%
“…Schwann cell electrophysiological investigations show ATP-evoked currents due to Ca 2+ -dependent K + and Cl − conductance via P2X 7 receptor activation and a P2X 7 non-selective cationic conductance [31]. P2X 7 receptor may be involved in local immunomodulation of axonal function by Schwann cells including regulation of cytokine release; this may be of particular relevance during peripheral nerve injury or neuropathies.…”
Section: Discussionmentioning
confidence: 99%
“…Initially it was thought that expression of the P2X 7 R was relatively restricted to cells of hematopoietic lineage, where it has been implicated in proliferation, giant cell formation, degranulation, cytolytic cell death and the ATP-dependent processing and release of cytokines such as interleukin-1β (IL-1β) (Laliberte et al, 1994;Falzoni et al, 1995;Surprenant et al, 1996;Chow et al, 1997;Rassendren et al, 1997;Virginio et al, 1999b;MacKenzie et al, 2001). More recently, however, the P2X 7 R has been found on diverse populations of cells, including Mueller cells (Pannicke et al, 2000), astrocytes (John et al, 2001;Panenka et al, 2001), Schwann cells (Colomar and Amedee, 2001), and neurons (Deuchars et al, 2001). In these cells, it has been implicated in the regulation of cytokine and chemokine expression, as well as in neuronal transmission, but pore formation and cytotoxicity has been less consistently observed.…”
Section: Introductionmentioning
confidence: 99%